Variation between natural head orientation and Frankfort horizontal planes in orthognathic surgery patients: 187 consecutive cases. Issue 9 (September 2021) - Hernández-Alfaro, F.; Giralt-Hernando, M.; Brabyn, P.J.; Haas, O.L.; Valls-Ontañón, A.
Abstract: The purpose of this study was to assess the relationship between the Frankfort horizontal (FH) and natural head orientation (NHO), their correlation between patients' malocclusion, and the impact of counterclockwise rotation (CCW) on the FH-NHO angle variation after orthognathic surgery. An evaluation of 187 consecutive patients was performed at the Maxillofacial Institute (Teknon Medical Center, Barcelona). FH-NHO° was measured pre- and postoperatively at 1 and 12 months, after three-dimensional (3D) superimposition using a software (Dolphin®). Patients were classified as follows: 3.2%, 48.7% and 48.1%, class I, II and III, respectively. Baseline FH-NHO° was significantly positive for patients with dentofacial deformities (2.73° ± 4.19 (2.12–3.33°, P  < 0.001). The impact of orthognathic surgery in FH-NHO° was greater in class II when compared with class III patients, with a variation of 2.04° ± 4.79 ( P  < 0.001) and −1.20° ± 3.03 ( P  < 0.001), respectively. FH-NHO° increased when CCW rotational movements were performed ( P  = 0.006). The results of this study suggest that pre- and postoperative NHO differs from FH in orthognathic patients. The angle between FH and NHO is significantly larger in class III than in class II patients at baseline, which converges after orthognathic surgery when CCW rotation is performed. Therefore, NHO should be used as the real horizontal plane when planning for orthognathic surgery.